Chijabyukpi-Tang Inhibits Pro-Inflammatory Cytokines and Chemokines via the Nrf2/HO-1 Signaling Pathway in TNF-α/IFN-γ-Stimulated HaCaT Cells and Ameliorates 2,4-Dinitrochlorobenzene-Induced Atopic Dermatitis-Like Skin Lesions in Mice - Lee, Ji-Hyun; Lim, Ji-Ye; Jo, Eun Hee; Noh, Hyeon Min; Park, Sunggu; Park, Min Cheol; Kim, Dae-Ki (Frontiers in Pharmacology, 2020)
Chijabyukpi-tang (CBT) is an oriental herbal formula consisting of three herbs (Gardeniae Fructus (Gardenia jasminoides J.Ellis.), Phellodendri Cortex (Phellodendron amurense Rupr.), Glycyrrhizae Radix (Glycyrrhiza uralensis Fisch.)) at the ratio of 2: 2: 1. CBT has traditionally been used to treat eczema with inflammation in Northeast Asia. The components of CBT have been shown to have anti-inflammatory and anti-oxidant properties, but the exact role and mechanism of CBT on atopic dermatitis (AD) remain unclear. In this study, we investigated the anti-inflammatory effect and mechanism of CBT in the HaCaT human keratinocyte cell line and investigated the anti-atopic effect in mice models of atopic dermatitis-like skin lesions. In the tumor necrosis factor alpha (TNF)-α/interferon (IFN)-γ-stimulated HaCaT cells, CBT inhibited the production of pro-inflammatory cytokines and chemokines and elevated the nuclear translocation of NF-E2 p45 related factors 2 (Nrf2) and subsequent production of heme oxygenase-1 (HO-1). CBT improved the symptoms of atopic dermatitis-like lesions in 2,4-dinitrochlorobenzene (DNCB)-treated mice by suppressing the levels of serum immunoglobulin E (IgE), and various pro-inflammatory cytokines and chemokines. The improvement effect of CBT on atopic dermatitis-like lesions can be predicted to be due to increased Nrf2 and HO-1 gene expression. These results suggest that CBT is an herbal medicine with the potential for use as a therapeutic agent for inflammatory skin diseases such as atopic dermatitis.